2022
DOI: 10.5812/aapm-127121
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Oxygen-Ozone Therapy and Platelet-Rich Plasma for the Treatment of Knee Osteoarthritis: A Meta-analysis and Systematic Review

Abstract: Context: This systematic review and meta-analysis evaluated the effect of the intra-articular injection of platelet-rich plasma (PRP) and oxygen-ozone therapy and provided an evidence-based methodology to treat KOA. Method: Databases, including Cochrane Library, PubMed, and EMBASE, were searched. The retrieval period was before 2021. Two reviewers performed the process of screening and data extraction. Mean differences were calculated [95% confidence interval (CI)] with an inverse-variance method and fixed eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Clinical studies have reported an efficacy of IAI of ozone in reducing short-term pain (up to 1 month of follow-up) in patients with KOA, when compared with noninvasive treatments or placebo injections, with loss of favorable effects after 3 months 6 . When directly compared ozone with CSs, 41 HA, 42 or PRP, 43 no differences were found among interventions up to 1-month follow-up; however, when comparing medium and long terms, HA 6,42 and PRP 43 were more effective in reducing pain and improving function than ozone injections. It has been reported that ozone is a safe intervention, with transient pain as the main secondary reaction and no severe side effects 44 .…”
Section: Intra-articular Injections Under Studymentioning
confidence: 99%
“…Clinical studies have reported an efficacy of IAI of ozone in reducing short-term pain (up to 1 month of follow-up) in patients with KOA, when compared with noninvasive treatments or placebo injections, with loss of favorable effects after 3 months 6 . When directly compared ozone with CSs, 41 HA, 42 or PRP, 43 no differences were found among interventions up to 1-month follow-up; however, when comparing medium and long terms, HA 6,42 and PRP 43 were more effective in reducing pain and improving function than ozone injections. It has been reported that ozone is a safe intervention, with transient pain as the main secondary reaction and no severe side effects 44 .…”
Section: Intra-articular Injections Under Studymentioning
confidence: 99%
“…While several traditional meta-analyses (16)(17)(18)(19) have demonstrated the advantages of non-drug treatment of KOA, these analyses have focused on the comparison of a single nondrug therapy with drugs or another non-drug therapy and have not compared multiple non-pharmacological interventions simultaneously. As the number of alternative treatment options increases, comparative effectiveness studies will be necessary.…”
Section: Introductionmentioning
confidence: 99%